牵引传动中乏油问题的研究 - 牛永生; 曹月影 (Jixie chuandong)
The lubricating condition is changed in 8 steps from the EHL condition to the dry condition to make clear the influence of the amount of oil on the performance of traction drive. Traction oil Daphne7074 is used for the lubricant. The slope of the initial traction curve increases with the decrease of the amount of oil at low pressure and approaches the value of the dry condition at high pressure. The maximum traction coefficient increases with the decrease of the amount of oil at low pressure and approaches the value of the EHL condition at high pressure. Small traction drive may be held even by the lubrication of the cloth from which oil is squeezed tightly.